Nanocompósitos a base de quitosana reforçados com nanofibras de Pinus sp. e Eucalyptus sp. - Hugen, Lisiane Nunes (2015)
Seeking alternatives for the use of forest resources in packaging industries, this study aimed to evaluate the effect of the inclusion of microfibrillated cellulose of Pinus sp. and Eucalyptus sp., at different concentrations, on the physical, mechanical, morphological, optical properties, as well as those of the composites prepared from chitosan (matrix). To obtain microfibrillated cellulose we used the mechanical fibrillation process. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to characterize the microfibrillated cellulose. The microstructural evaluation of composites was performed using scanning electron microscopy (SEM) and Xray diffraction (XRD). Physical and mechanical properties were also evaluated. The results showed that, after the mechanical processing of Pinus sp. e Eucalyptus sp. pulps, a reduction of approximately 99% occurred in the average diameter of the obtained microfibrillated cellulose. The addition of 10% of reinforcement improved 105% and 75% tensile strength, for composites with microfibrillated cellulose of Eucalyptus sp. and of Pinus sp., respectively. An increase of 75% and 69% occurred in the modulus of elasticity for microfibrillated cellulose of Eucalyptus sp. and of Pinus sp., respectively. The addition of microfibrillated cellulose decreased transparency of the composites. The values of water solubility and permeability to water vapor of the composites with high microfibrillated cellulose content showed a significant decrease.